2019
DOI: 10.1002/etc.4616
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution, Growth Dilution, and Species‐Specific Bioaccumulation of Organic Ultraviolet Absorbents in Wildlife Freshwater Fish in the Pearl River Catchment, China

Abstract: Tissue distributions and body-size dependent and species-specific bioaccumulation of 12 organic ultraviolet absorbents (UVAs) were investigated in 9 species of wildlife freshwater fish from the Pearl River catchment, South China. The concentrations of the 12 UVAs were from 109 to 2320 ng/g lipid weight in the fish tissue samples. The UVAs 2-hydroxy-4methoxybenzophenone (BP-3), octocrylene (OCR), UV531, and 5 benzotriazole UV stabilizers (UVP, UV329, UV234, UV328, and UV327) were detected in more than half of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 47 publications
4
23
0
Order By: Relevance
“…Still, these observations suggest the potential for either the excretion of translocated particles, as has been demonstrated with nanoparticles, or growth dilution. Growth dilution of contaminants is a known phenomenon, demonstrated with mercury in salmonid and organic ultraviolet absorbents in Barbell chub and Redbelly tilapia . Laboratory studies that increase our understanding of particle uptake and excretion, including the consideration of species-specific differences, are critical to confirm our results.…”
Section: Resultssupporting
confidence: 55%
“…Still, these observations suggest the potential for either the excretion of translocated particles, as has been demonstrated with nanoparticles, or growth dilution. Growth dilution of contaminants is a known phenomenon, demonstrated with mercury in salmonid and organic ultraviolet absorbents in Barbell chub and Redbelly tilapia . Laboratory studies that increase our understanding of particle uptake and excretion, including the consideration of species-specific differences, are critical to confirm our results.…”
Section: Resultssupporting
confidence: 55%
“…The accumulation of these contaminants is considered to be diet-specific. 40 , 55 , 63 Some studies have suggested that bottom feeders tend to accumulate more BZT-UVs and Ar-SAs than fishes with other feeding habits. 5 , 54 , 55 In addition, lake sturgeon from this study were older (16–25 years old) than northern pike (2–7 years old), suggesting different exposure histories to contaminants.…”
Section: Resultsmentioning
confidence: 99%
“…While the combined proportion in gill and muscle was around 20 percent for most BUVSs. Similarly,Peng et al (2020) observed that the concentration of BUVSs in sh liver is apparently higher than those in other tissues like muscle, bladder and fat. Other compounds, like organophosphate ame retardants (OPFRs), poly brominated diphenyl ethers (PBDEs), and FQs, are also reported previously to be more likely to accumulate in metabolically active sh tissues (liver or kidney) instead of in metabolically inactive tissues (muscle)(Bekele et al, 2021;Chen et al, 2019;Kim et al, 2015).…”
mentioning
confidence: 79%